2019
DOI: 10.1159/000496975
|View full text |Cite
|
Sign up to set email alerts
|

Probable Etoricoxib-Induced Severe Thrombocytopenia: A Case Report

Abstract: Objective: To describe a case of likely etoricoxib-induced severe thrombocytopenia. Clinical Presentation and Intervention: A 32-year-old woman was referred to our hospital for disseminated petechial rash after 7 days of therapy with etoricoxib. At admission, the patient’s platelet count was 3,000/mm3. At Naranjo’s scale correlation between thrombocytopenia and drug was considered as “probable.” With the diagnostic tests performed we did not find other causes of thrombocytopenia. Etoricoxib was disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…The present study found lower platelet COX-2 expression in adult ITP patients and a positive correlation between COX-2 protein expression and platelet count. These clinical results were hardly reported in ITP but consistent with previous studies beyond ITP, as there has been a reported case of severe drug-induced immune thrombocytopenia (DITP) caused by the selective COX-2 inhibitor etoricoxib [ 34 ]. And meta-analyses of COX-2 inhibitors in treating non-small cell lung cancer concluded that COX-2 inhibitors may increase the risk of thrombocytopenia [ 35 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…The present study found lower platelet COX-2 expression in adult ITP patients and a positive correlation between COX-2 protein expression and platelet count. These clinical results were hardly reported in ITP but consistent with previous studies beyond ITP, as there has been a reported case of severe drug-induced immune thrombocytopenia (DITP) caused by the selective COX-2 inhibitor etoricoxib [ 34 ]. And meta-analyses of COX-2 inhibitors in treating non-small cell lung cancer concluded that COX-2 inhibitors may increase the risk of thrombocytopenia [ 35 37 ].…”
Section: Discussionsupporting
confidence: 89%